MORPHOLOGICAL DESCRIPTION OF MAST CELLS’ REPRESENTATION AT CHRONIC CATARRHAL GINGIVITIS - Yeroshenko, G.A.; Gasyuk, N.V.; Kalinichenko, M.V. (World of Medicine and Biology, 2010)
Neuroparacrine mechanism of adjusting of blood vessels’ activity is carried out by mast cells. Output of neurohumors of inflammation – bioactive matters, look as a starting mechanism of inflammatory process in gum, that determines the further picture of inflammatory process . Leading role in the process of synthesis, accumulations and excretions of neurohumors of inflammation tissue basophilies play.
Keywords: mast cells; gum; gingivitis; mediators